2001
DOI: 10.1029/2000je001370
|View full text |Cite
|
Sign up to set email alerts
|

Mars Global Surveyor Thermal Emission Spectrometer experiment: Investigation description and surface science results

Abstract: Abstract. The Thermal Emission Spectrometer (TES) investigation on Mars GlobalThe TES data are calibrated to a 1-o-precision of 2.5 -6 X 10 -8 W cm -2 sr-1/cm -•, 1.6 x 10 -6 W cm -2 sr -•, and -0.5 K in the spectrometer, visible/near-IR bolometer, and IR bolometer, respectively_. These instrument subsections are calibrated to an absolute accuracy of-4 x 10 -8 W cm -2 sr-•/cm -• (0.5 K at 280 K), 1-2%, and -1-2 K, respectively. Global mapping of surface mineralogy at a spatial resolution of 3 km has shown the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
782
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 938 publications
(812 citation statements)
references
References 102 publications
18
782
3
Order By: Relevance
“…Known rock compositions/types include basalt, basaltic andesite, hematite, quartz, andesite, phyllosilicates, sulfates, layered sedimentary deposits, etc. (e.g., Malin and Edgett, 2000;Bandfield et al, 2000;Christensen et al, 2000Christensen et al, , 2001aChristensen et al, ,b, 2005Rieder et al, 2004;Gendrin et al, 2005). Therefore, there is very little confidence that SNC meteorites provide an even and unbiased sampling of the Martian surface.…”
Section: Geologic and Mineralogic Information Of Claritas Risementioning
confidence: 99%
“…Known rock compositions/types include basalt, basaltic andesite, hematite, quartz, andesite, phyllosilicates, sulfates, layered sedimentary deposits, etc. (e.g., Malin and Edgett, 2000;Bandfield et al, 2000;Christensen et al, 2000Christensen et al, , 2001aChristensen et al, ,b, 2005Rieder et al, 2004;Gendrin et al, 2005). Therefore, there is very little confidence that SNC meteorites provide an even and unbiased sampling of the Martian surface.…”
Section: Geologic and Mineralogic Information Of Claritas Risementioning
confidence: 99%
“…Although the dikes are too small to directly obtain quantitative mineralogy using Thermal Emission Spectrometer (TES) data (spatial resolution 3 Â 8 km [Christensen et al, 2001]), the highest model concentrations of Fo 68 olivine within the wrinkle ridged plain and impact ejecta are $20% using the maps from Koeppen and Hamilton [2008]. The concentrations of Mg-rich olivine in the dikes are likely $20% based on the assumption of compositional similarity.…”
Section: Discussionmentioning
confidence: 99%
“…To address this we conducted a series of mineral precipitation experiments from O 2 -poor solutions saturated with both calcite and hannebachite and found that inhibition of carbonate precipitation occurs at even lower values of pSO 2 :pCO 2 than predicted. This implies that even if SO 2 were not abundant enough to influence Noachian climate, it may provide an explanation for the scarcity of carbonate minerals at outcrop abundance [Christensen et al, 2001], other than in laterally restricted environments that may not represent prevailing early Martian surface conditions [Ehlmann et al, 2008]. Because this explanation for the scarcity of carbonates does not require acidic conditions, it may also account for the occurrence of early phyllosilicates [Poulet et al, 2005], which require near-neutral pH to form [Velde, 1995].…”
Section: Introductionmentioning
confidence: 99%